Effect bio-fertilizer on growth performance of rice / Siti Zubaidah Ahmad Hanafi - Ahmad Hanafi, Siti Zubaidah (Faculty of Plantation and Agrotechnology, 2016)
Rice is staple food in Asia. The agriculture sectors become more challenges because demand of rice was increased over a year. Rice growth and yield highly depend on nutrient management. Nowadays bio-fertilizer was recommended to use as alternative way to enhance plant nutrient uptake. This review paper highlighted the effect of bio-fertilizer on the growth of rice. Applications of bio-fertilizer on rice have showed a positive effect on the growth of rice. Different types of microorganism play different role in rice growth and development. Some microorganisms in bio-fertilizer help increase mineral absorption and fixing nitrogen. The sufficient nutrient will ensure the improvement in rice production.